Mind-Building Sculpture and Cognitive Engagement - Akpowowo Bensandy Ozokeraha (Journal of Arts, Humanities and Social Science, 2025)
This paper examines the idea of mind-building sculpture, that is a specialty of sculpture that is beyond aesthetics and utility to explore the intellectual, emotional and psychological topographies of the viewer. It discusses how the modern and classical sculptors incorporate a cognitive framework into the sculptural form, material and spatial engagement and sculpture turns out to become a generator of reflection, knowledge and self-transformation. The study relies on art history, phenomenology, and neuroscience to note the great potential of sculpture in shaping physical territory, as well as the human mind.